Can Green Finance Drive the Development of the Green Building Industry?—Based on the Evolutionary Game Theory - Li, Shaoliang; Zheng, Xiazhong; Zeng, Qin (Sustainability, 2023)
The construction industry has a significant impact on the environment, and green buildings provide an effective means of reducing environmental impact. Green finance can facilitate industrial transformation and upgrading, reduce construction costs, attract investment, and promote green industry development. However, traditional financing models still dominate the financing of green building projects, even if they are not in line with the core principles of green building. To solve this problem, this paper establishes a three-party evolutionary game model, which, based on the assumption of finite rationality, considers three core stakeholders: bank and financial institutions, developers, and consumers. The conditions for evolutionary stable equilibrium are identified through an equilibrium analysis of the strategic behavior of each subject, followed by a replication dynamic analysis. Simulation analysis was used to study the effects of key parameters on cooperative behavior and evolution. The results of the study show that (1) The high initial willingness of bank and financial institutions and consumers has a significant driving effect on the market. (2) When the market willingness is high, the government can steer the market towards the desired goal at relatively low policy costs. (3) With the support of green finance, green buildings can still flourish even if the return is slightly lower than traditional building projects. The results of the study reveal cooperative behavior and its evolutionary patterns, which help stakeholders coordinate their goals and promote the development of the green building industry.